PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS HEYZINE PADA MATERI HAK DAN KEWAJIBAN SEKOLAH DASAR - Harmuli, Sri; Faizal Chan; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a Heyzine-based learning media for the topic “Rights and Obligations at Home and at School” for fourth-grade elementary students. This research employed a Research and Development (R&D) approach using the 4D model, which consists of Define, Design, Develop, and Disseminate stages; however, the study was limited to the Develop stage with restricted dissemination. The Define stage included front-end analysis, learner analysis, task analysis, concept analysis, and the formulation of learning objectives. The Design stage involved creating a storyboard and selecting visual elements to be integrated into the Heyzine platform. The Develop stage consisted of validation by media experts, material experts, and language experts, followed by small-group trials involving fourth-grade students. The results indicate that the Heyzine-based learning media met all feasibility criteria with a “Highly Feasible” category based on expert validation. Small-group trials also showed that the media was highly practical, easy to use, engaging, and effective in helping students understand the concepts of rights and obligations. Therefore, Heyzine-based learning media can serve as an innovative tool to enhance motivation and improve the quality of Civic Education learning in elementary schools.